Elucidation of an α-glucosidase inhibitor from the peel of Allium cepa by principal component analysis. Issue 4 (3rd April 2019) - Ogi, Kayako; Sumitani, Hidenobu
ABSTRACT: We conducted liquid chromatography-mass spectrometry measurements on hot-water extracts of peel from different varieties of Allium cepa . Some quercetin glycosides were identified as potential α-glucosidase inhibitors by principal component analysis of the liquid chromatography-mass spectrometry data. α-Glucosidase inhibitory activity assays identified quercetin-4ʹ- O -glucoside as an α-glucosidase inhibitor.